Replication of genetic associations of chemotherapy-related cardiotoxicity in the adjuvant NSABP B-31 clinical trial - Advani, Pooja P.; Ruddy, Kathryn J.; Herrmann, Joerg; Ray, Jordan C.; Craver, Emily C.; Yothers, Greg; Cecchini, Reena S.; Lipchik, Corey; Feng, Huichen; Rastogi, Priya; Mamounas, Eleftherios P.; Swain, Sandra M.; et al. (Frontiers in Oncology, 2023)
Background: The cardiotoxic effects of doxorubicin, trastuzumab and other anticancer agents are well known, but molecular genetic testing is lacking for early identification of patients at risk for therapy-related cardiac toxicity. Methods: Using the Agena Bioscience MassARRAY system, we genotyped TRPC6 rs77679196, BRINP1 rs62568637, LDB2 rs55756123, RAB22A rs707557, intergenic rs4305714, LINC01060 rs7698718 and the CBR3 rs1056892 (V244M), (previously associated with either doxorubicin or trastuzumab-related cardiotoxicity in the NCCTG N9831 trial of anthracycline based chemotherapy +/- trastuzumab), in 993 patients with HER2+ early breast cancer from the NSABP B-31 trial of adjuvant anthracycline based chemotherapy +/- trastuzumab. Association analyses were performed with outcomes of congestive heart failure (N=29) and maximum decline in left ventricular ejection fraction (LVEF) using logistic and linear regression models respectively, under an additive model with age, baseline LVEF and previous use of hypertensive medications as covariates. Results: Associations of maximum decline in LVEF in the NCCTG N9831 patients did not replicate in the NSABP B-31 patients. However, TRPC6 rs77679196 and CBR3 rs1056892 were significantly associated with congestive heart failure, p<0.05, with stronger associations observed in patients treated with chemotherapy only (no trastuzumab) or in the combined analysis of all patients relative to those patients treated with chemotherapy + trastuzumab. Conclusions: TRPC6 rs77679196 and CBR3 rs1056892 (V244M) are associated with doxorubicin-induced cardiac events in both NCCTG N9831 and NSABP B-31. Other variants previously associated with trastuzumab-related decline in LVEF failed to replicate between these studies.